Development of a pathology-supported genetic test for improved clinical management of patients diagnosed with multiple sclerosis - Jalali Sefid Dashti, Mahjoubeh (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScMedSc (Pathology. Chemical Pathology))--University of Stellenbosch, 2010.